PENINGKATAN MOTIVASI KADER DAN TOKOH MASYARAKAT KECAMATAN KOTO TANGAH DALAM MENSUKSESKAN SKRINING KANKER SERVIKS DI MASA PANDEMI COVID-19 - rhandyka Rafli; Tia Reza; Primadella Fegita (Stikes Syedza Saintika Padang, 2021)
Cervical cancer is a massive health burden in Indonesia because of its mortality, morbidity, and disability. Most of the cervical cancer deaths were caused by delayed diagnosis and a lack of early screening. Padang city screening program achievement is meager compared to the national standard. During pandemic covid -19, the number is getting worse. One of the strategies is to collaborate with health cadets and community leaders. Our activity focused on boosting their understanding of the danger of cervical cancer and the benefit of early detection. We encourage health cadet and community leaders to be active to invites women in their community to take an early detection for cervical cancer, but also considering the health protocols during pandemic covid -19 Keyword: cervical cancer, early screening, Covid 19